An interactive packaging with augmented reality technology to boost promotion case study: Lc Merchandising Sdn Bhd (Upin Ipin Store) / Nur Hanis Ezan - Ezan, Nur Hanis (Universiti Teknologi MARA, Perak, 2020)
LC Merchandising Sdn. Bhd. (LCM) is the company that produces the 3D animated series "Upin & Ipin". All products by LCM are licensed and approved by LCP. LCM's merchandise comes in a wide variety of products ranging from stationery, apparel to bags and toys. These come with more than 100 selections and one of the products is Upin Ipin Squeezy toy. In the past, plastic bags were used as the packaging for this product. Therefore, the objective of this research is to develop an interactive printed-based solution which is a box packaging for the Upin Ipin Squeezy toy. This newly-designed packaging comes with a value-added and high impact innovation that incorporates augmented reality (AR) technology. The processes involved research into opportunity identification, concept exploration, and refinement. The outcome of this research is hoped to stimulate and boost interest among the young consumers.